TEKNIK PORTOFOLIO DAN INSTRUMEN ASESMEN DALAM PENDIDIKAN ANAK USIA DINI - Farihah, Elyaum (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
Portfolio assessment is an ongoing assessment based on a collection of information that shows the development of students' abilities in a certain period. The information can be in the form of student work from the learning process that is considered the best by students. Portfolio assessment basically assesses the work of students individually over a period for a subject. At the end of a period the work is collected and assessed by the teacher and students. Based on this development information, teachers and students themselves can assess the development of students' abilities and continue to make improvements. Thus, the portfolio can show the progress of students' learning progress through their work, including: essays, poems, letters, compositions, music.